Social prescribing to improve health and well-being of patients presenting with non-medical health related social needs in primary care: Study protocol of a multi-center randomized controlled pragmatic feasibility trial - Hendrik Napierala; Niklas Jeske; Stephanie Roll; Juliane Köberlein-Neu; Wolfram J. Herrmann (PLoS ONE, 2025)
Background Non-medical health related social problems are highly prevalent in primary care. Even though there is a wide range of non-clinical support and services available in German communities, which can potentially meet the needs of the affected patients, there are no formalized connections between these services and primary care. One potential solution is social prescribing (SP) providing general practitioners (GPs) with a non-medical referral option, which can accompany existing treatments to improve health and well-being. The goal of this trial is to test the feasibility of a randomized controlled trial and potential benefit of SP in the primary care setting in Germany. Methods This trial is designed as a multi-center, two-armed, open, exploratory, individually randomized (2:1) controlled, pragmatic, feasibility trial. 300 adult patients presenting with one or more non-medical health-related social needs will be recruited in GP practices in Berlin and Brandenburg, Germany. Participants in the intervention group will receive a referral to a link worker. The link worker assesses the social needs, agrees on a goal and sets up an action plan together with the patient. The link worker then connects the patient to suitable non-clinical support and services in the community (e.g., volunteering opportunities). The GP is informed about the actions taken through a feedback form. Participants in the control group will receive treatment-as-usual plus a brochure with information about local offers of non-clinical support and services in the community. Follow-up per patient is 6 months with measurements at 3 and 6 months. Primary endpoint is the feasibility of the trial measured by (1) proportion of participants who have at least one appointment with the link worker (intervention arm only), (2) proportion of participants that drop out of the trial before the 6-month follow-up (both arms). Secondary endpoints include further feasibility endpoints (acceptability, practicality, demand), clinical endpoints such the health status and wellbeing, and a goal-based outcome for the intervention group. The trial is accompanied by a process evaluation, including qualitative episodic interviews with patients and stakeholders. Furthermore, a description of selected economic consequences of SP and its intervention costs will be conducted. Discussion This trial will assess the feasibility of implementing SP in the German primary care setting and will provide information and data necessary to plan a confirmatory trial. Implementing SP could be an adequate solution to address psychosocial problems in primary care. Trial registration German Clinical Trials Registry, DRKS-ID: DRKS00034654. Registered on August 27th.2024. https://drks.de/search/en/trial/DRKS00034654